2006
DOI: 10.1038/sj.sc.3101923
|View full text |Cite
|
Sign up to set email alerts
|

Cerebro-spinal decompression sickness: report of two cases

Abstract: Both divers developed cerebro-spinal dysfunction. They had encephalopathy (manifested by loss of consciousness), which indicates bilateral cerebral dysfunction. DCS can occur even when dives are conducted according to the procedures described by the US Navy. The use of high-dose steroids has not been formally tested in DCS; their use is controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 4 publications
2
12
0
4
Order By: Relevance
“…In a case study involving a male diver who died from severe DCS after a rapid ascent from 120 m, extensive gas embolism in cerebral and spinal arteries as well as cerebrospinal fluid spaces using postmortem CT and MRI were found (20). This case study has been confirmed in another recent study, which also found cerbrospinal dysfunction in two divers (11). Thus, given this evidence and the fact that the heart receives the ANS inputs from the spinal cord, we speculate that the injury to the spinal cord is most likely the culprit in the impairment of the ANS seen in our swine with DCS.…”
Section: Discussionsupporting
confidence: 68%
“…In a case study involving a male diver who died from severe DCS after a rapid ascent from 120 m, extensive gas embolism in cerebral and spinal arteries as well as cerebrospinal fluid spaces using postmortem CT and MRI were found (20). This case study has been confirmed in another recent study, which also found cerbrospinal dysfunction in two divers (11). Thus, given this evidence and the fact that the heart receives the ANS inputs from the spinal cord, we speculate that the injury to the spinal cord is most likely the culprit in the impairment of the ANS seen in our swine with DCS.…”
Section: Discussionsupporting
confidence: 68%
“…In fact, on follow-up 1 and 2 weeks after the decompression, changes in T 2 were found in brain stem and thalamus among decompressed animals. These delayed findings are in accordance with previously published clinical reports, where MRI abnormalities, especially increased T 2 indicating focal CNS injuries, have been found several weeks after the decompression (Reuter et al 1997; Hierholzer et al 2000; Jallul et al 2007). These studies showed MRI abnormalities mostly in the spinal cord, and this is despite the fact that MRIs made during the first 24 h after onset of symptoms (Jallul et al 2007) were normal.…”
Section: Discussionsupporting
confidence: 93%
“…However, the lack of signs of injury on acute MRI is not surprising, since all but one of the animals showed no neurological signs at that time. In previous studies, focal CNS injuries on conventional MRI were found in the presence of neurological symptoms and signs (Yoshiyama et al 2007; Jallul et al 2007; Gronning et al 2005; Reuter et al 1997). Moreover, even in the presence of clinical neurological signs suggesting brain involvement, abnormalities on cerebral MRI are uncommon, occurring only in 25 % of the patients in one study (Reuter et al 1997) and none in another (Gronning et al 2005).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the overall incidence of diving‐related DCS is low, 7 we have managed to collect the data and MRI findings of seven patients who have been diagnosed with and treated for DCS at our local hyperbaric facility. This paper will describe the clinical presentation, MRI spinal cord findings, treatment administered and outcome of these patients.…”
Section: Introductionmentioning
confidence: 99%